Поетичні діалоги: Леся Українка та Іван Стешенко - Александрова, Г. (Філологічний дискурс, 2018)
У статті аналізуються основні мотиви поезії Івана Стешенка,
що репрезентувала розвиток естетичних тенденцій кінця ХІХ –
початку ХХ ст., простежуються її новаторські риси та суголосність
із творчістю Лесі Українки. У пропонованій розвідці розглянуто
ключові образи, які відображають складну систему духовного життя
обох поетів, їхні відчуття, систему цінностей і є вагомим елементом
художнього світу і Лесі Українки, й Івана Стешенка. Доведено, що
спільними концептуальними компонентами художньої картини
світу обох поетів, у якій переплітаються неокласичні і
неоромантичні тенденції, є окремі мотиви, ідеї, образи (сльози, зоря,
думка, пісня, муза та ін.). Lesya Ukrainka and Ivan Steshenko were modern and bright figures in the
literary and socio-political life of Ukraine in the late nineteenth and early twentieth
centuries, writers, translators, politicians. Their personal communication, creative
and everyday contacts were quite tight. Both in artistic views and in nationalpolitical
convictions they were like-minded intellectuals-Ukrainians who created the
spiritual field of Ukrainian culture. The article discusses the leading concepts of
their creativity, which often coincide, and their poems develop similar themes and
use the same motives and images. The article analyzes the main motives of Ivan
Steshenko’s poetry, which represented the development of aesthetic tendencies of the
late nineteenth and early twentieth centuries, traces its innovative features and
conscientiousness with the works of Lesia Ukrainka. Part of such coincidences is a
tribute to the «wind time», and some have emerged as a consequence of influence.
The search for such traces, the tracing of the dialogue of the texts of the primordial
and forgotten poet, leads to wider generalizations: the features of national literature,
the influence of the time on the artistic thinking of the artist. At the same time, he
reminds of the need to always pay attention to the significance of a seemingly
artistic secondary as a self-worth literary phenomenon, without studying which it is impossible to outline the true spiritual field of Ukrainian literature, to construct a complete model of the national literary process. Parallels of Steshenkov’s poetry with
Lesia Ukrainka’s poetry are not in vain. They are the children of one historical and literary era, therefore they have stable universal symbols of mood, similar spiritual values orientations of artistic thinking, elements of positivism and modernism
correlating, interconnected neo-classical and neo-romantic tendencies, of course, originally artistically solved by each artist. For both artists, the Word is the center of the microcosm, it is able to change the world. In general, coincidences and analogies in their poetry are much more than differences and contrasts. The key images that reflect the complex system of the spiritual life of both poets, their senses, the system of values and are a significant element of the semiosphere of the artistic world and Lesia Ukrainka and Ivan Steshenko are considered. It is proved that the common conceptual components of the artistic picture of the world of both poets are separate motives, ideas, images (tears, star, dance, song, muse, etc.).